Aesthetic theory - Adorno, Theodor W., 1903-1969.; Adorno, Gretel; Tiedeman, Rolf. (Minneapolis, Minn. : University of Minnesota Press, 1997)
The culmination of a lifetime of aesthetic investigation, Aesthetic Theory is Adorno's major work, a defense of modernism that is paradoxical in its defense of illusion. In it, Adorno takes up the problem of art in a day when "it goes without saying that nothing concerning art goes without saying." In the course of his discussion, Adorno revisits such concepts as the sublime, the ugly, and the beautiful, demonstrating that concepts such as these are reservoirs of human experience. These experiences ultimately underlie aesthetics, for in Adorno's formulation "art is the sedimented history of human misery."
Art, Society, Aesthetics -- Situation -- On the Categories of the Ugly, the Beautiful, and Technique -- Natural Beauty -- Art Beauty; Apparition, Spiritualization, Intuitability -- Semblance and Expression -- Enigmaticalness, Truth Content, Metaphysics -- Coherence and Meaning -- Subject-Object -- Toward a Theory of the Artwork -- Universal and Particular -- Society -- Paralipomena -- Theories on the Origin of Art -- Draft Introduction.
Includes bibliographical references and index.
Keywords: Aesthetics